Pengaruh Gaya Kepemimpinan dan Kompensasi terhadap Kinerja Kinerja Karyawan Koperasi Ambatoea Jaya Bogor - Kristianti, Lily Setyawati (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
Employee performance is a critical factor in determining the success and sustainability of an organization, especially in cooperative institutions that rely heavily on human resources. Therefore, understanding the factors that influence employee performance is essential. This study aims to examine the effect of leadership style and compensation on employee performance. A quantitative method with an associative approach was employed to conduct this research. The population and sample consisted of employees of Koperasi Ambatoea Jaya Bogor, specifically in the Terminal Inspection Unit-T1. Instrument testing included validity and reliability tests. Classical assumption tests such as normality, multicollinearity, autocorrelation, and heteroscedasticity were also applied to ensure the robustness of the data analysis. The data were analyzed using simple linear regression, multiple linear regression, correlation coefficients, and the coefficient of determination. Hypothesis testing was conducted using t-tests and F-tests. The results showed that both leadership style and compensation have a positive and significant effect on employee performance. This indicates that better leadership and fair compensation are likely to improve employee outcomes. Simultaneously, these two variables contribute significantly to performance, though other external factors also play a role. The findings highlight the importance of a holistic human resource management approach in enhancing employee performance and achieving organizational goals.